Exploring the impact of demand and supply-side interventions on energy decarbonization of freight transportation: a research based on G20 nations - Zhang, Boyuan (Frontiers in Energy Research, 2024)
Through quantitative modeling, the study established a dynamic supply & demand system from freight demand, renewable energy production, alternative new energy, renewable energy consumption and carbon dioxide emissions to assess the impact of demand-side & supply-side changes on energy decarbonization. The results indicate that adjusting the freight volumes of railway and aviation, renewable energy electricity supply, and the use of alternative new energy sources have varying degrees of impact on decarbonization in transportation. Through interventions on the demand side of freight volumes, CO2 emissions from transportation decrease to levels below those before the intervention-induced fluctuations, while consumption of renewable energy increases to levels above those before the adjustment.